ATG proteins: Are we always looking at autophagy?. Issue 12 (1st December 2016) - Mauthe, Mario; Reggiori, Fulvio
ABSTRACT: Autophagy is an intracellular degradation pathway that is regulated by the autophagy-related (ATG) proteins. For a long time it has been thought that ATG proteins were exclusively required for autophagy, but recent experimental evidence has revealed that these proteins are part of other cellular pathways, individually or as a functional group. To estimate the extent of these so-called unconventional functions of the ATG proteins, we decided to perform an unbiased siRNA screen targeting the entire ATG proteome and used viral replication as the readout. Our results have uncovered that a surprisingly high number of ATG proteins (36%) have a positive or negative role in promoting virus replication outside their classical role in autophagy. With the increasing knowledge about ATG protein unconventional functions and our investigation results, the interpretations about the possible involvement of autophagy in cellular or organismal functions that solely rely on the depletion of a single ATG protein, should be considered cautiously.